Non-interference trusted model based on processes - ZHANG Xing1; CHEN You-lei2; SHEN Chang-xiang2 (Tongxin xuebao)
A novel abstract model for the design of trusted computing platform system was proposed.By using the basic idea of non-interference theory as reference and introduces the reasoning method of process algebra, thus abstracting the system as processes, actions, states and outputs, and giving the formal definition of the trusted of process running.Process isolation trusted theorem was verified formally.Furthermore, by associating process with system state, the definition and the theorem of system running trusted was proposed.The model was established by logic reasoning and independent of special security mechanism and enforcement.The trust of the running system can be realized by any method which satisfies the conditions of the model.